Symposium 2: The uncodings of ANT: Mobilities of digital data - Thompson, Terrie Lynn (Proceedings of the International Conference on Networked Learning, 2014)
One of the basic tenets of Actor Network Theory (ANT) is to “follow the actors”. However, coded materialities (the digital in all its forms, including software, devices, networks, artefacts, and algorithms) are notoriously fickle. Digital things are often described as unbounded, evasive, distributed, and constantly mutating (Kallinikos, Aaltonen & Marton, 2010). Indeed, the web, as portrayed by Czerski (2012), seems to simply exist as flow. So how do networked learning researchers reckon with these mobilities and multiplicities? As a form of posthumanist theorizing, ANT-inspired researchers attend to how the assemblings of “thingly gatherings” co-constitute enactments of everyday practices with, in, around, and through human actors. Therefore, ANT seems to offer an ontological questioning and framing that can engage with the fluidity of the digital. In this short paper (and Pecha Kucha presentation), I call on ANT to explore how the digital interposes data within the research process—freezing, thawing, excluding, including—beckoning researchers to attend to the sociality of data. The discussion that follows the presentation will draw on real-time examples from the other papers in this symposium to explore the mobilities of digital data. In moving to a posthuman framing, data—a blackboxed materiality of research projects—becomes much more complex. A sociomaterial reading of data suggests it is a relational effect: becoming in a particular moment because of juxtapositions of multiple networks. Such a conceptualization of data raises several questions. First, how does one theorize the role of the digital in the production of social data and the research process? Second, the encoding of data has amplified its mobility and performativity: it is distributed, often public, fragmented, and entangled in multiple recursive circulations. It takes on new forms and energies. Tensions become apparent, for example as dynamic digital data, at home in the wilderness of the web, is translated to the archived (or frozen) data that appears in screen captures or pdf journal articles. Here, the mobility and fluidity of data (the state of always becoming and creating ongoing movements in understanding) wrestles with practices of solidifying data (freezing or tethering: settling down and settling into a particular locality). This tension provides one entry point for examining the mobilities and socialities of data.